COMBINING TRADITIONAL PRACTICAL TRAINING WITH MODERN TECHNOLOGICAL APPROACHES IN PHYSICAL EDUCATION CLASSES - Молотильнікова, В.; Ложенко, К.В. (Modern engineering and innovative technologies, 2025)
This article explores the importance of combining traditional practical activities with modern technological approaches in physical education. It analyzes the effectiveness of integrating innovative technologies—such as mobile applications, online platfor